AA MICRO BUSINESS EMPOWERMENT BY USING SOCIAL MEDIA - Kunto Inggit Gunwan; Mataji Mataji (ABDIMAS, 2022)
Since the enactment of the Asean Economic Community (MEA) at the end of 2015 should encourage all economic actors, including SMEs and Micro Enterprises, to improve themselves in order to improve the quality of production of both goods and services. If this is not done, then Indonesia is a "soft" market for other Asean countries because Indonesia has the largest population (population size) in Asean, which is no less than 270 million people. SMEs and Micro Enterprises, which are the embodiment of the people's economic democracy, will be very hit when the flow of goods and services from various Asean countries invades the Indonesian market. Realizing this, empowering SMEs and Micro Enterprises is a must and a necessity to be able to find a national identity that has a comparative advantage and a competitive advantage. This activity begins with identifying the existing problems and then looking for a solution method, the method used is to provide training and assistance. The result that has been achieved is the ability of AA's business to optimize its sales by using social media. Thus, the AA Micro Enterprises can improve their capabilities in the field of simple bookkeeping and business management. The existence of these outputs is an indication of increasing business empowerment.